Unlocking the secrets of banded coral snake (Calliophis intestinalis, Malaysia): A venom with proteome novelty, low toxicity and distinct antigenicity - Tan, Kae Yi; Liew, Jia Lee; Tan, Nget Hong; Quah, Evan S.H.; Ismail, Ahmad Khaldun; Tan, Choo Hock (Elsevier, 2019)
The Asiatic coral snakes are basal in the phylogeny of coral snakes. Although envenoming by the Asiatic coral snakes is rarely fatal, little is known about their venom properties and variability from the American coral snakes. Integrating reverse-phase high performance liquid chromatography and nano-liquid chromatography-tandem mass spectrometry, we showed that the venom proteome of the Malaysian banded or striped coral snake (Calliophis intestinalis) was composed of mainly phospholipases A2 (PLA2, 43.4%) and three-finger toxins (3FTx, 20.1%). Within 3FTx, the cytotoxins or cardiotoxins (CTX) dominated while the neurotoxins’ content was much lower. Its subproteomic details contrasted with the 3FTx profile of most Micrurus sp., illustrating a unique dichotomy of venom phenotype between the Old and the New World coral snakes. Calliophis intestinalis venom proteome was correlated with measured enzymatic activities, and in vivo it was myotoxic but non-lethal to mice, frogs and geckos at high doses (5–10 μg/g). The venom contains species-specific toxins with distinct sequences and antigenicity, and the antibodies raised against PLA2 and CTX of other elapids showed poor binding toward its venom antigens. The unique venom proteome of C. intestinalis unveiled a repertoire of novel toxins, and the toxicity test supported the need for post-bite monitoring of myotoxic complication. Significance: Malaysian banded or striped coral snake (Calliophis intestinalis) has a cytotoxin (CTX)-predominating venom proteome, a characteristic shared by its congener, the Malayan blue coral snake (Calliophis bivirgata). With little neurotoxins (NTX), it illustrates a CTX/NTX dichotomy of venom phenotype between the Old World and the New World coral snakes. The low toxicity of the venom imply that C. intestinalis bite envenoming can be managed via symptomatic relief of the mild to moderate pain with appropriate analgesia. Systemically, the serum creatine kinase level of patients should be monitored serially for potential complication of myotoxicity. The distinct antigenicity of the venom proteins implies that the empirical use of heterologous antivenom is mostly inappropriate and not recommended.